Employing Light Fidelity in Iot-Based Healthcare System - Marwan S. M. Al-Dabbagh; Awos Kh. Ali (Theory and Applications of Engineering Research Vol. 6, 2024)
Light Fidelity (Li-Fi) is an emerging technology that has been in transferring data packets in the Internet of Things (IoT) applications. During the COVID-19 pandemic, most healthcare institutes around the world try to manage the rapid increase of patients’ numbers. The healthcare team may not have the ability to monitor patients’ stats properly around the clock with the conventional sight techniques. During the era of Internet, communication becomes quick, secure and reliable through wired and wireless networks. Wireless networks have become more relevant in general domestic applications as well as health care applications. In this paper, a healthcare monitoring framework to exchange health data between bio-sensors and terminals by employing Li-Fi technology is proposed; The proposed framework exploits Li-Fi technology to transmit data packets towards network terminal and then to a cloud platform. It is intended for use in highly dense healthcare institutes where the number of patients is high. Exploiting the Li-Fi transmitting technology to establish connection avoids the need for the high cost of other transmission technologies such as Wi-Fi and provides less complexity in terms of network configuration and shorter end-to-end latency. We evaluate the proposed framework in a real-life environment using bio-sensors (tagged on patients’ bodies) and Li-Fi communication model (for network infrastructure), these two components are connected to a computing terminal to help health staff monitor patients, in addition, the computing terminal is connected to a cloud platform to allow remote monitoring and provides more computing resilience. The proposed framework shows superior performance in real-world scenarios compared to conventional communication medium (Wi-Fi), additionally, a comprehensive analysis has been conducted to show the differences between the two selected transmitting technologies (Li-Fi and Wi-Fi). Since Li-Fi uses infrared and visible light spectrum for data communication, it achieves the shortest E2E delay in comparison to Wi-Fi, resulting in faster data transmission and packet delivery. As far as network throughput is concerned, both Wi-Fi and Li-Fi achieved similar results. The proposed model enables healthcare staff to monitor patients’ status 24x7 and the related health information is updated effortlessly.